Student Perceptions of Using Spotify’s English Songs as a Medium for Learning Vocabulary in Higher Education University - Lathifa Faza Ramadhani; Intan Permata Hapsari (IKIP Siliwangi, 2026)
This study aims to investigate students’ perceptions of using English songs as a medium for vocabulary learning through a digital music platform. The research employed a descriptive quantitative design using a survey method. The participants were 30 second-semester students from the English Department at a state university in Semarang, selected through purposive sampling. Data were collected using a questionnaire consisting of 20 Likert-scale items and analyzed using descriptive statistics in the form of percentages. The findings indicate that students generally have positive perceptions toward the use of songs for vocabulary learning. Most students consider songs to be useful, enjoyable, and effective in helping them understand and acquire new vocabulary. In addition, songs were found to increase students’ motivation and engagement, which contribute to vocabulary improvement. These results suggest that songs can provide meaningful language input and create a more engaging learning experience. Therefore, integrating songs into language learning activities is recommended to support students’ vocabulary development.